1995
DOI: 10.1111/j.1600-9657.1995.tb00464.x
|View full text |Cite
|
Sign up to set email alerts
|

Replantation of 400 avulsed permanent incisors. 4. Factors related to periodontal ligament healing

Abstract: 400 avulsed and replanted permanent teeth were examined for periodontal ligament (PDL) healing, using standardized radiographic and clinical examination procedures (i.e. percussion test and mobility test). The effect of various clinical factors was examined, such as age and sex of the patient, type of tooth replanted, presence of crown fracture or bone fracture, stage of root development (including apical diameter and length of the pulp), type and length of extra-alveolar storage, clinical contamination of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
713
5
49

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 598 publications
(794 citation statements)
references
References 38 publications
27
713
5
49
Order By: Relevance
“…Certain studies have reported good prognoses after tooth transplantation, with recent success rates exceeding 90% (7,16). However, other studies have demonstrated failure of approximately 23% of transplanted teeth, most commonly because of dentoalveolar ankylosis (4)(5)(6)(7)(8). Therefore, we aimed to investigate whether LIPUS could regenerate PDL and prevent dentoalveolar ankylosis after autotransplantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Certain studies have reported good prognoses after tooth transplantation, with recent success rates exceeding 90% (7,16). However, other studies have demonstrated failure of approximately 23% of transplanted teeth, most commonly because of dentoalveolar ankylosis (4)(5)(6)(7)(8). Therefore, we aimed to investigate whether LIPUS could regenerate PDL and prevent dentoalveolar ankylosis after autotransplantation.…”
Section: Discussionmentioning
confidence: 99%
“…However, autotransplantation is more advantageous than prostheses such as dentures or implant placement in terms of success and periodontal sensation in the alveolar bone; this type of transplantation induces formation of new supporting tissue, continued root formation, eruption, and maintenance of occlusal contact with opposing teeth (1)(2)(3). Use of transplantation is increasing, and its clinical success rates are improving as well (4)(5)(6)(7)(8). Sugai et al reported a success rate of approximately 90% for autotransplantation; however, in the other 10% of cases, the prognosis was poor, and one-third of these cases experienced postoperative dentoalveolar ankylosis (7).…”
Section: Introductionmentioning
confidence: 99%
“…A recent evidencebased appraisal of the literature indicates that splint type and duration were not generally a significant variable in relation to healing outcomes [24]. Although, ankylosis and replacement resorption may be observed with a long-term splinting, significant improvements outcomes with short-term spliting have not been shown [25][26][27]. Now it's recommended that the tooth be splinted for up to two weeks contrary to six weeks as before [24].…”
Section: Splintmentioning
confidence: 99%
“…2 Clinical reports have indicated that the prognosis is best for teeth replanted within 5 minutes of avulsion. [3][4][5][6] Most often replantation is not done immediately, because of injury circumstances. Extended non-physiological storage of avulsed teeth before replantation results in necrosis of the PDL and consequent healing by replacement root resorption.…”
Section: Introductionmentioning
confidence: 99%